Processes taking place during the preparation and use of electrospun PLA fibers and their effect on controlled drug release - Yi Lan; Luo Sheng; Cui Lu; Budai-Szűcs Mária; Móczó János; Pukánszky Béla (2022)
PLA fibers containing metronidazole as the active component were produced by electrospinning from a solvent mixture of dichloromethane (DCM) and dimethyl sulfoxide (DMSO). The DMSO content of the spinning solution changed between 0 and 25 vol% in 5 vol% steps. The fibers were dried at different temperatures, and processes taking place during fiber production and drying were followed by thermogravimetric analysis and differential scanning calorimetry. The morphology and structure of the fibers were studied by microscopy and X-ray diffraction. The mechanical properties of fiber mats and the release of the drug were also determined as a function of processing and drying parameters. The results showed that several processes take place during the production and subsequent handling of the fibers including the evaporation of the solvent (DMSO), the crystallization of the polymer, the changing of composition, phase separation and the consequent partitioning of the drug. The crystalline structure of the fibers changes considerably during drying which determines their mechanical properties. The rate of evaporation and crystallization is in the same order of magnitude. The rate of both processes increases considerably with temperature, but does not depend strongly on the amount of DMSO in the spinning solution. Both the amount of the drug released and the rate of release cover a wide range depending on the parameters of the preparation technology. The large range of mechanical and functional properties obtained allows the control of the kinetics of drug release to some extent.
Keywords: Farmakológia és gyógyszerészet